PENGGUNAAN METODE ALTMAN Z-SCORE MODIFIKASI UNTUK MEMPREDIKSI KEBANGKRUTAN PT BANK NEO COMMERCE, TBK - Windya Angelin; Muspa Muspa; Sujatmiko Sujatmiko (Program Pasca Sarjana IBK Nitro, 2023)
The problem in this research is that PT Bank Neo Commerce Tbk will experience a large net loss in 2021. The purpose of this research is to find out how the Altman Z-Score method predicts bankruptcy in the company PT Bank Neo Commerce, Tbk. The data used in this study is secondary data in the form of the financial statements of PT Bank Neo Commerce, Tbk for 2018-2021 which are accessed through the website www.idx.co.id. The results of the study used the Altman Z-Score method in 2018 - 2021 where the company is in a dangerous zone in 2018, 2019 and 2021 because the Z-Score value is in the Z range < 1.1. Whereas in 2020 the results obtained from the Altman Z-score, namely the Z-Score value is in the vulnerable 1.1 < Z < 2.6, meaning the company is in a gray zone.